2012
DOI: 10.1186/1472-6920-12-126
|View full text |Cite
|
Sign up to set email alerts
|

Nervous system examination on YouTube

Abstract: BackgroundWeb 2.0 sites such as YouTube have become a useful resource for knowledge and are used by medical students as a learning resource. This study aimed at assessing videos covering the nervous system examination on YouTube.MethodsA research of YouTube was conducted from 2 November to 2 December 2011 using the following key words “nervous system examination”, “nervous system clinical examination”, “cranial nerves examination”, “CNS examination”, “examination of cerebellum”, “balance and coordination exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 16 publications
0
60
0
5
Order By: Relevance
“…9 The ease of uploading videos, constant improvement of Web site content to support online sharing, and quick access to content are the factors that facilitate the growth and appeal of the YouTubee Web site. 10 As the use of the YouTubee Web site has become popular in dentistry and medicine, the quality of YouTubee content has been assessed in a variety of studies. The results of these studies are important in terms of revealing the level of information that patients acquire about a particular subject.…”
Section: Introductionmentioning
confidence: 99%
“…9 The ease of uploading videos, constant improvement of Web site content to support online sharing, and quick access to content are the factors that facilitate the growth and appeal of the YouTubee Web site. 10 As the use of the YouTubee Web site has become popular in dentistry and medicine, the quality of YouTubee content has been assessed in a variety of studies. The results of these studies are important in terms of revealing the level of information that patients acquire about a particular subject.…”
Section: Introductionmentioning
confidence: 99%
“…YouTube videos have been noted as useful for medical education, particularly to medical students for clinical examinations of the nervous, cardiovascular and respiratory systems 16,17 . This also appears to be the case regarding surgical education.…”
Section: Resultsmentioning
confidence: 99%
“…In social media research, participants can be identified either directly or through the internet links related to the websites used, which arouses concerns about the definition of privacy in social media research and the need to evaluate each research study in context and on its own merits [30][31][32][33][34]. Therefore, if the study enables the disclosure of subjects' responses or statements in a way that might reveal their identity or their place of residence or that exposes them to risks or potential harms (e.g., political, financial, social)-such as research using videos from the war in Syria-it must be approved by an institutional ethical research review committee.…”
Section: Specific Ethical Concerns In Health-related Researchmentioning
confidence: 99%